1998
DOI: 10.4278/0890-1171-12.5.307
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Impact of Incentives in Population-Based Smoking Cessation Programs: A Review

Abstract: Incentive-based smoking cessation programs that target an entire community have the advantage of reaching a large and diverse group of smokers. They may, however, attract only smokers who are already motivated to quit. Realistically, incentive-based programs aimed at the general population can expect 1% of all their smokers to quit smoking. Quit rates among participants may initially be high (i.e., mean quit rate of 34% at 1-month follow-up) but decrease over time (i.e., mean rate of 23% at 1 year). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 31 publications
1
31
0
7
Order By: Relevance
“…Although community organizations may also find this a cost-effective intervention, it may be more difficult to fund these incentive programs through community-based mechanisms. Most commonly, financial incentives have been used to promote smoking cessation in community and worksite settings through a combination of monetary payments, competitions, entries into lotteries, and prizes of cash or merchandise (17). Interpretation of quit rates in these programs is difficult as many of them measure quit rates conditional on program enrollment and are based on nonexperimental designs.…”
Section: Financial Incentives and Smoking Cessation Cancer Epidemiol mentioning
confidence: 99%
See 1 more Smart Citation
“…Although community organizations may also find this a cost-effective intervention, it may be more difficult to fund these incentive programs through community-based mechanisms. Most commonly, financial incentives have been used to promote smoking cessation in community and worksite settings through a combination of monetary payments, competitions, entries into lotteries, and prizes of cash or merchandise (17). Interpretation of quit rates in these programs is difficult as many of them measure quit rates conditional on program enrollment and are based on nonexperimental designs.…”
Section: Financial Incentives and Smoking Cessation Cancer Epidemiol mentioning
confidence: 99%
“…However, it is unknown whether such incentives can work in the populations of patients who are at highest risk for smoking-related illnesses (long-term heavy smokers), treated in the type of primary care clinical settings where most outpatient care is delivered. Previous studies to evaluate this have been limited by nonexperimental designs, self-reported cessation outcomes, and weak incentives (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…35 Second, a range of factors, including the use of financial incentives, demographic factors (eg, ethnicity, age), and smoking-related behavioral characteristics (eg, readiness to quit, amount smoked), distinguish between those who enroll in smoking cessation programs and those who decline. Bains et al 38 and Hennrikus et al 30 reported that monetary incentives increased enrollment among eligible smokers in a cessation program. Woods et al 39 found that, among African-American smokers eligible for a smoking cessation study, decliners were more likely to be men, younger, less educated, and unemployed.…”
mentioning
confidence: 99%
“…A review on the use and impact of incentives in population-based smoking cessation programs 32 showed that larger incentives were more effective in both influencing smokers' participation and motivating them to quit and remain smoking-free. Elixhauser 33 also reviewed the cost-effectiveness of smoking cessation methods and concluded that interventions specifically aimed at a particular subgroup appeared to be more cost-effective.…”
Section: Reaching Eligible Participants and Quality Of Recruitment Stmentioning
confidence: 99%